2007
DOI: 10.1093/jxb/erl259
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency differently affects metabolic responses in soybean roots

Abstract: Iron deficiency responses were investigated in roots of soybean, a Strategy I plant species. Soybean responds to iron deficiency by decreasing growth, both at the root and shoot level. Chlorotic symptoms in younger leaves were evident after a few days of iron deficiency, with chlorophyll content being dramatically decreased. Moreover, several important differences were found as compared with other species belonging to the same Strategy I. The main differences are (i) a lower capacity to acidify the hydroponic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 45 publications
13
68
0
6
Order By: Relevance
“…through which they chelate the Fe 3+ from the hemolymph, leaving the insect deprived of Fe 3+ , resulting death of the host. Previously, Römheld and Marschner (1981) and Zocchi et al (2007) have suggested that Fe 3+ chelating potential and chemical stability of the siderophores can be exploited for the plant growth promotion, as siderophores chelate iron, making it unavailable to pathogens and thereby suppressing the growth of microbial pathogens in specific niches surrounding plants and improving plant health and growth indirectly. Others have hypothesized that siderophores chelate Fe +3 , significantly increasing its mobility in the soil and making it more accessible to plants (Römheld & Marschner 1981;Dobbelaere et al 2003).…”
Section: Siderophore Production Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…through which they chelate the Fe 3+ from the hemolymph, leaving the insect deprived of Fe 3+ , resulting death of the host. Previously, Römheld and Marschner (1981) and Zocchi et al (2007) have suggested that Fe 3+ chelating potential and chemical stability of the siderophores can be exploited for the plant growth promotion, as siderophores chelate iron, making it unavailable to pathogens and thereby suppressing the growth of microbial pathogens in specific niches surrounding plants and improving plant health and growth indirectly. Others have hypothesized that siderophores chelate Fe +3 , significantly increasing its mobility in the soil and making it more accessible to plants (Römheld & Marschner 1981;Dobbelaere et al 2003).…”
Section: Siderophore Production Assaymentioning
confidence: 99%
“…GAs act as signaling molecules which degrade the DELLA protein complex and allow the phytochrome interacting factors to bind the gene promoters and regulate gene expression (Davière et al 2008). Siderophore production is another characteristic of the M1021 through which bacteria chelate Fe 3+ , making it unavailable to pathogens as well as increase it mobility in rhizosphere and thereby, improve plant growth attributes (Römheld & Marschner 1981;Zocchi et al 2007).…”
Section: Plant Growth Promotion By P Temperata M1021mentioning
confidence: 99%
“…A variety of metabolic alterations have been reported to occur in response to Fe starvation, such as an induction of CO 2 dark fixation, an increase in amino acid and S-adenosyl-Met (SAM) biosynthesis, and an accumulation of organic acids in roots (Thimm et al, 2001;Buckhout and Thimm, 2003;Zocchi et al, 2007;López-Millán et al, 2009). Increased production of ethylene and nicotianamine (NA), an important micrometal chelator in plant cells that plays a crucial role in Fe homeostasis and transport (Klatte et al, 2009) from SAM and chelation of Fe by citrate during long-distance transport, may be the cause for some of these changes.…”
mentioning
confidence: 99%
“…La PEPCasa constituye, de este modo, la principal enzima relacionada con el aporte de compuestos intermediarios del ciclo de los ácidos tricarboxílicos en tejidos no fotosintéticos bajo condiciones deficitarias de Fe (Chollet et al, 1996). La ausencia de Fe también estimula la actividad de otros enzimas relacionados con el ciclo de Krebs y la ruta glicolítica (Zocchi et al, 2007;López-Millán et al, 2000Jelali et al, 2010b) y en algunos casos también se ha observado la inducción de la expresión de los genes correspondientes (Thimm et al, 2001). …”
Section: Biosíntesis De áCidos Orgánicosunclassified
“…Esquema del ciclo de biosíntesis de ácidos orgánicos en las células de la raíz. (Zocchi et al, 2007;Jelali et al, 2010b). Jones (1998) sugiere que incluso con bajas tasas de exudación de citrato, la cantidad de Fe 3+ solubilizado es suficiente para satisfacer las necesidades férricas de la planta.…”
Section: Biosíntesis De áCidos Orgánicosunclassified